Performance of samatha self help groups in the empowerment of rural women in Ulloor panchayat - Meera M J (Department of Agricultural Extension, College of Agriculture, 2001)
The study was carried out in Ulloor panchayat of Thiruvananthapuram district of Kerala among four major Samatha production units identified. Twelve groups were selected based on probability proportionate to size from among the four major production units. The study aimed to' analyse the performance of characteristics and profile characteristics of members, to study the structure and functions of Samatha groups, perception of officials (including people's representatives) about Samatha groups, constraints faced by members and officials and suggestions for improvement. The respondents consisted of 120 members selected from the 12 production units, out of the four major units identified. The second category of respondents included officials and people's representatives associated with the working of Samatha groups. Two control groups consisting of 15 respondents from Samatha banks and 15 respondents of rural women who are not members of any group. The dependent variables for the study were the dimensions of . empowerment namely leadership propensity, self confidence, employment